Metode Pembelajaran Filsafat Hindu: Studi Teks Filsafat India Klasik dan Proyeksinya pada Pembelajaran Filsafat Hindu Dewasa ini - Ni Kadek Surpi; I Ketut Ardana (Jurnal Penelitian Agama Hindu, 2022)
The method of learning philosophy is an important key in understanding the tree of knowledge of Indian philosophy. This method has been explored by sages and writers since classical times as an integral part of the discussion of darśana. However, this method does not seem to have been adopted in learning Hindu philosophy in Indonesia. This research is a text study that discusses the Hindu philosophy learning method described by Hindu philosophers and thinkers as a learning tool. Data obtained through literature study by examining several classical Indian philosophical texts, data analysis using Content Analysis. An important finding of this research is that the methodology of learning Hindu philosophy must begin by studying the three starting-points known as praṣṭana-trayā namely the upaniṣads, Bhagavad-gitā and the sūtra texts. Starting from the three starting-points of Vedānta (three starting-points of Vedānta) as praṣṭana-trayā namely upaniṣad, Bhagavad-gitā and Brahmā-Sūtra. In Vedanta it is called the triple cannon of Vedānta. Without following this procedure, failure will overshadow the students of philosophy. Therefore, learning praṣṭana-trayā is the starting point in an effort to understand the scientific tree of Hindu philosophy. These three starting points for learning philosophy should be adopted properly in order to improve thinking skills, reasoning skills, including improving writing, debate, argumentation and discussion skills.